Birth Anthropometry Characteristics of Hypospadias Patients in Palembang, Indonesia - ziske maritska; Savero Evan Abisha Evan Abisha; Triwani Triwani (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2019)
ABSTRACT. Background. Hypospadias is one of the most common urogenital anomaly in males. The etiology is poorly understood, but is believed to be multifactorial where Intra Uterine Growth Restriction (IUGR) is one of the suspected risk factors, leading to low birth weight and low birth length in affected patients. Objective. This study aims to identify the birth anthropometry characteristics of hypospadias patients who visited RSUP. Dr. Mohammad Hoesin Palembang. Materials and Methods. This was an observational descriptive study with cross sectional design. This study included hypospadias patients with detailed birth characteristics in RSUP Dr. Mohammad Hoesin Palembang during the period of 2012-2015. Results. Out of 106 hypospadias patients, only 19 (17.92%) of them presented with detailed birth characteristics. There were 12 (63,2%) patients with low birth weight and 7 (36,8%) patients with normal birth weight. There were 10 (52,6%) patients with low birth length and 9 (47,4%) patients with normal birth length. The mean birth weight is 2442 grams and the mean birth length is 46,9 centimeters. Conclusion. The majority of hypospadias patients in this study showed a low birth weight and low birth length, signalling an accordance to the existing theory. Keywords: Hypospadias, birth anthropometry, characteristics